PARA UMA PAZ SEM FIM : Um estudo, sócio-político e teológico, da tipologia messiânica nas perícopes de Isaías 7,10-17 e 8,23-9,6. - Santos, Suely Xavier dos (2005)
The act of anointing, which the term Messiah comes from, was a custom of ancient Middle East peoples, and it was assimilated by Israel. The Old Testament, however, reinterpreted such act of anointing. At first, The King was titled The Anointed, maxiah;. Accordingly, King David was the one who originated the messianic mentality in Israel. Concernin g messianic theology, the prophet Isaiah became an important exponent. He addressed to the upper classes of Jerusalem and proposed the anointed of Yahweh, in replacement for the king of The House of David. That was so because the messianism had also become a movement of resistance for the fulfilment of justice and rights, which culminated in lack of peace. In his way, Isaiah offers too a new perception of messianism, namely, a rupture with the House of David (7,17). Such a Messiah was not under the human categories of a good, strong warrior king, but rather under the guidance of the Spirit of Yahweh. Therefore, the Messiah could be a child one (7,14; 9,5). The aim of this dissertation is to track along the way from the arising of the anointed, or the act of anointing, to the Isaiah´s conception of messiah. The development of this work will show, in the end, the messianic typology presented by the prophet Isaiah as from the pericopes 7,10-17 and 8,23-9,6.(AU)